Effects of combined therapy with atorvastatin and polyunsaturated omega-3 fatty acids on lipid profile, lipoprotein-associated phospholipase A2 and thromboxane - G. F. Piksina; Yu. A. Shuvalova; V. I. Kaminnaya; Yu. V. Dotsenko; V. N. Titov; V. V. Kukharchuk; A. I. Kaminny (Кардиоваскулярная терапия и профилактика)
Aim. To study the effects of the combined therapy with atorvastatin and polyunsaturated omega-3 fatty acids (omega-3 PUFA) on lipid profile, lipoprotein-associated phospholipase A2 (Lp-PLA (2)), and thromboxane B2. Material and methods. The study included 60 patients with coronary heart disease (CHD), randomised into two groups: Group I (n=29) receiving atorvastatin monotherapy; and Group II (n=31) receiving combined therapy with atorvastatin (10 mg/d) and omega-3 PUFA (1 g/d). At baseline, 12 and 24 weeks later, all participants underwent the assessment of lipid profile, serum levels of Lp-PLA (2), and plasma levels of thromboxane B2. Results. Adding omega-3 PUFA to atorvastatin therapy did not change the lipid-lowering action of the latter, with an exception of a greater triglyceride level reduction (-32 %; p=0,001 vs. the baseline). In both groups, six-month therapy was associated with a significant decrease in Lp-PLA (2) level (-33 % and -34 % for monotherapy and combined therapy groups, respectively; р=0,002 for both comparisons). Thromboxane B2 concentration decreased by 26 % (р=0,07) in Group I and by 62 % in Group II (р=0,02), compared to baseline levels. Conclusion. Combined therapy with atorvastatin and omega-3 PUFA was associated with decreased levels of atherogenic lipoproteins, Lp-PLA (2) and thromboxane B2, which can result in cardiovascular risk reduction.